Identification of neoantigen epitopes in cervical cancer by multi-omics analysis - Jing Yuan; Na Xu; Xueqi Gong; Jihui Ai; Kezhen Li; Yingyan Han (European Journal of Medical Research)
Abstract Background Tumor vaccines enhance the immune response and cytotoxicity of tumor-specific T cells and show promising clinical therapeutic efficacy. Although most cervical cancer cells express HPV-related oncoproteins, some do not. Additionally, neoantigens worth attracting attention for cervical cancer (CC) may hold the potential for breakthroughs in the development of cervical cancer vaccines. Methods A comprehensive computational analysis was conducted based on the tumor genome, transcriptome, and proteome data from 284 cervical cancer samples obtained from the TCGA database. Frequently mutated genes were identified. The levels of immune cell infiltration were analyzed using RNA-seq data, high-frequency mutated genes were identified as candidate genes that were significantly related to immune infiltration. Focusing on MHC class I epitopes recognized by CD8 + T cells, we predicted potential neoantigen peptides using the NetMHCpan-4.0 and NetCTL-1.2 algorithms. To further confirm the immunogenicity of the synthesized peptides, we performed flow cytometry and real-time PCR in vivo to examine markers of T cell activation and cytotoxicity. We also stimulated PBMC from patients with the corresponding HLA type with the synthesized peptides using an ELISpot assay. Results We identified 30 highly mutated genes, among which TTN, PRKDC, PCLO, MUC17, HUWE1, RYR2, and CREBBP positively correlated with immune cell infiltration into the tumor microenvironment. PCLO exhibited higher protein expression in tumor tissues than in the corresponding normal tissues, making it a potential tumor antigen. The PCLO peptides SISRFTLEK and LSEAGHFFY exhibited the highest predicted scores among the cancer antigens and strong immunogenicity in vivo. Conclusion Our analysis highlights the potential of PCLO as a candidate gene for enhancing immune cell infiltration and activating immune responses in tumors. The peptides SISRFTLEK (PCLOL4169F) and LSEAGHFFY (PCLOA3000S) are promising targets for tumor vaccines.